2015
DOI: 10.1080/00927678.2015.1034611
|View full text |Cite
|
Sign up to set email alerts
|

Democracy Promotion in India's Foreign Policy: Emerging Trends and Developments

Abstract: Democracy promotion has never been an integral element of India's foreign policy. The pursuit of its national interests in the international arena has traditionally revolved around security, trade, and energy issues. This article demonstrates, however, that in recent times India has taken a more active stance in promoting and supporting democracy abroad. It identifies the specific ways in which India has engaged in democracy promotion and support abroad. Nevertheless, 'realist' concerns about strategic and eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…India is the only regional secular democracy which can help American against Islamic militancy (Gupta, 2005). India wants US to compel Taliban and Al Qaeda in Afghanistan, Pakistan and Nepal for regional stability and democracy (Mazumdar, 2014).…”
Section: The Us-india Growing Tiesmentioning
confidence: 99%
“…India is the only regional secular democracy which can help American against Islamic militancy (Gupta, 2005). India wants US to compel Taliban and Al Qaeda in Afghanistan, Pakistan and Nepal for regional stability and democracy (Mazumdar, 2014).…”
Section: The Us-india Growing Tiesmentioning
confidence: 99%
“…However, in reality, there is an urgent need to overcome the "political development gap". While Asia is also home to another democratic emerging power, India, it tries to avoid framing its foreign policy in terms of supporting democracy due to geopolitical considerations (Mazumdar and Statz 2015). Indonesian foreign policy elites have observed that Indonesia's initiative for regional partnership can fill this gap.…”
Section: Sharing Democracy Through Bali Democracy Forummentioning
confidence: 99%